Application of Intelligent Disability Rating Method Based on Big Data Cloud Platform - WANG Yulong (康复学报)
Action plan on aging is a major strategic issue in China. Rapid and accurate identification of the disabled elderly and evaluation of the disability level is the basis of targeted interventions in aging. In this paper, we have reviewed the studies on the methods and existing problems of disability rating at home and abroad. We found that there was no unified standard for the identification and evaluation of the disabled elderly, and there were many problems in the current evaluation methods, such as tedious evaluation contents, complex evaluation steps, high requirements for the evaluators, time-consuming evaluation process, abstract and complicated evaluation results, inability of patients and their families to conduct self-evaluation and poor guidance for practical work, etc. Based on the theory of "accurate identification of disabled people", our research team developed the national standard of "Longshi assessment method of activities of daily living" (Longshi Scale), which is in line with China's national conditions and cultural background. This scale has the characteristics of "simplicity" "quickness" "accuracy" and "time-saving", which can provide a reliable basis for the identification of the disabled elderly and the rating of disability. This study focused on the design concept, evaluation process, evaluation criteria and intelligent applications (big data cloud platform, mobile applications, WeChat in-app programs, etc.) of Longshi Scale. The scale has good application prospects in the disability evaluation of the elderly, disability prevention and health care, employment policy making, aging industry development, nursing human resources allocation and other field.